MISI GEREJA DALAM KONTEKS PLURALITAS DI INDONESIA - Hariprabowo, Yakobus (LOGOS, 2003)
Proclamation is the permanent priority of mission. Church cannot elude Christ's explicit mandate, nor deprive men and women of the "Good News" about their being loved and saved by God. The unity of the human race and the universal salvific will of God, as expressed in the single divine origin and the single divine goal, are the foundations of the relationship between the Church and non-Christian religions. Church on earth is not equivalent to the Kingdom of God. However the risen Lord sent the Holy Spirit to the Church, the spiritual and salvific forces of the Kingdom are present in the Church and throughout the Church then brings about devine salvation in the world.